Der Einfluß der Religion auf Politik und Gesellschaft in Afrika - Sundermeier, Theo (Zeitschrift für evangelische Ethik, 1993)
The author explains four patterns concerning the relation between the church and the political institutions in Afrika. These patterns have be seen against the background of the original Ontocratic unity in premale societies, which all rulers in Africa favorite in an hidden way. Colonialism promotes the separation between political and religious life, nationalism, however, restores the unity. In South-Afrika a prophetic dualism is turning against the theocratic ideology of the Boers. All in all a relation of critical loyality is coming into existence in Africa.